Mourning in feminine procreation and sterility: A psychodynarnic and projective approach - Clement, Anne K. (2000)
This paper uses a psychoanalytical framework to analyze women's mourning with regard to procreation and sterility. The psychodynamic factors related to this topic are described and illustrated with the presentation of a clinical case. This case was assessed with interviews and the Rorschach Inkblot Test according to the French system (de Tychey, 1994). The analysis of the data allows the discussion of the theoretical concepts and addresses the importance of the variety of conflicts that interfere with the desire of procreating. The findings are also discussed from an ethical point of view regarding the role that the clinician plays when he has to face these types of severe cases.